AOF-Village sérère - François-Edmond Fortier (Wikimedia Commons, 1928)
Notice image issue de Wikimedia Commons. Titre: AOF-Village sérère. "Afrique Occidentale - Dans un village Cérère"
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale